Getting the message out: Information and communication technologies and agricultural extension - Giulivi, Nicoletta; Harou, Aurélie; Gautam, Shriniwas; Güereña, David T. (Wiley, 2023)
There has been much optimism about the potential of information and communication technologies (ICTs) to provide agricultural extension services to remote households. Yet, little is known about how different communication methods fare, and, moreover, whether different segments of the population adopt information communicated via different means equally. We conduct a randomized controlled trial comparing the effectiveness of three ICTs—radio, voice response messages, and a smartphone app—with traditional extension training in communicating fertilizer management practices across four districts in rural Nepal. We find that farmers in the smartphone app and the extension training programs are on average 8.4 and 13 percentage points more likely to adopt topdressing fertilizer practices compared to control farmers, statistically significant at the 1% and 5% levels, respectively. Farmers in the smartphone app treatment achieve the highest agronomic literacy test scores, 7.8 percentage points higher than the control, statistically significant at the 1% level. In contrast, farmers receiving radio or voice response messages were not more likely to adopt the same fertilizer recommendations nor show improved specific or general agronomic knowledge relative to control farmers. Our results suggest that smartphone apps are more cost effective at inducing farmer knowledge and technology adoption than extension trainings. Heterogeneous treatment effects, however, reveal that a targeted ICT approach may be more effective in disseminating extension advice.